Current Status of Comprehensive Chromosome Screening for Elective Single-Embryo Transfer. (1st June 2014) - Wu, Ming-Yih; Chao, Kuang-Han; Chen, Chin-Der; Chang, Li-Jung; Chen, Shee-Uan; Yang, Yu-Shih
Abstract : Most in vitro fertilization (IVF) experts and infertility patients agree that the most ideal assisted reproductive technology (ART) outcome is to have a healthy, full-term singleton born. To this end, the most reliable policy is the single-embryo transfer (SET). However, unsatisfactory results in IVF may result from plenty of factors, in which aneuploidy associated with advanced maternal age is a major hurdle. Throughout the past few years, we have got a big leap in advancement of the genetic screening of embryos on aneuploidy, translocation, or mutations. This facilitates a higher success rate in IVF accompanied by the policy of elective SET (eSET). As the cost is lowering while the scale of genome characterization continues to be up over the recent years, the contemporary technologies on trophectoderm biopsy and freezing-thaw, comprehensive chromosome screening (CCS) with eSET appear to be getting more and more popular for modern IVF centers. Furthermore, evidence has showen that, by these avant-garde techniques (trophectoderm biopsy, vitrification, and CCS), older infertile women with the help of eSET may have an opportunity to increase the success of their live birth rates approaching those reported in younger infertility patients.